Penerapan Media Wordwall Untuk Meningkatkan Fokus Anak ADHD Dalam Pembelajaran Inklusif - Aslamiyah Aslamiyah; Ahmad Khoiri; Vava Imam Agus Faisal (FKIP UNSULTRA, 2026)
This study aims to describe the application of Wordwall media in inclusive learning and analyze its role in improving the learning focus of children with ADHD at SC Klab Wonosobo Kindergarten. This study uses a qualitative method with a descriptive approach. The subjects of the study were children with ADHD with hyperactive and inattentive characteristics, while informants consisted of the principal, class teachers, and assistant teachers. Data collection techniques included observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions using source triangulation techniques and techniques to ensure data validity. The results showed that before the application of Wordwall media, children with ADHD had difficulty maintaining focus, were easily distracted, and were less active in learning. After the application of Wordwall media in core learning activities, there were significant changes in learning behavior, namely increased focus, enthusiasm, active participation, and involvement of children in learning activities. Wordwall media, which is based on interactive games with visual elements, audio, and quiz activities, has been proven to be able to create a more enjoyable and interesting learning atmosphere for children. In addition, this media also contributes to children's social development through activities such as waiting for turns, working together, and obeying game rules. The success of implementing wordwalls is influenced by conducive classroom conditions, educator competence, and collaboration between the classroom teacher and the assistant teacher. Therefore, wordwalls can be an effective interactive learning tool to support inclusive learning for children with ADHD in early childhood education.